Perovskitas híbridas de haleto sob condições extremas de pressão e temperatura - Vasconcelos, Francisco Nailson Farias de (2023)
Recently, perovskite-like organic-inorganic hybrid compounds have become promising in developing semiconductors with applications in optoelectronics. Such materials exhibit wide structural versatility and tunable optical properties, either through their intrinsic structural properties or induced by extreme pressure and temperature conditions. In this thesis, we used the slow evaporation method to obtain two new perovskite-like compounds, AlaPbBr3.H2O (Ala= [NH3-CH(NH2)-COOH]+) and (PEA)2Cs2Pb3Br10 (PEA=[C6H5-CH2-CH2-NH3]+), whose structural, optical, and vibrational properties were investigated under extreme conditions of pressure and temperature. In the case of the compound AlaPbBr3.H2O, we observed that its unusual structure [PbBr6]4-, is responsible for forming a wide direct bandgap of Eg = 3.6 eV. Furthermore, substantial evidence supports the hypothesis of self-trapped excitons (STEs) formation. This phenomenon was proven by observing a strong exciton-phonon coupling at low temperatures. In addition, Raman spectroscopy and photoluminescence measurements under high pressures indicated a structural phase transition around 2.2 GPa as the factor responsible for a shift in the emission band energy. In the case of the compound (PEA)2Cs2Pb3Br10, we observed a structure belonging to the Ruddlesden-Popper phase, presenting a direct bandgap of Eg=2.5 eV and an emission profile susceptible to temperature and pressure variations. It is observed that the structural transition around 100K is the mechanism for a sudden change observed in the emission spectrum as a function of temperature. Associated with this phenomenon, the emergence of additional emission peaks around 60K suggests the formation of new electronic recombinations. An attenuated exciton-phonon coupling is also observed, possibly related to the effects of the inorganic layer in its structure. Under pressure, it is observed for this compound that two phase transitions at 0.5 GPa and 2.5 GPa are responsible for the formation and suppression of the emission bands, respectively. Additionally, variations in the number of Raman modes suggest a correlation between pressure-induced distortions in the [PbBr6]4- octahedra and the emission dynamics of this compound.